A method for preparing a high flux capillary pore cellulose composite membrane

CN122912686APending Publication Date: 2026-10-16KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611148136.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]目前,基于纤维素的分离膜制备方法主要有以下局限:(1)直接真空抽滤法所得膜在干燥过程中因纤维间强烈的氢键作用和水的毛细管力引发孔道收缩与结构致密化,导致孔隙率大幅下降,最终造成水通量显著受限;(2)化学交联法常消耗纤维素表面的亲水性羟基,降低膜的亲水性,且残留交联剂可能造成环境与健康风险;(3)聚合物共混法面临纳米纤维素在有机溶剂中分散性差、与疏水聚合物基质相容性不佳的问题,纳米纤维素倾向于被聚合物完全包埋,无法充分发挥其表面亲水性和纳米通道效应;(4)界面聚合法制备的膜通量受到致密皮层的极大限制,且涉及有毒有机溶剂

Benefits of technology

1、毛细孔形成方法简单:本发明毛细孔高通量纤维素膜通过简单的浸渍再生过程即可获得,其孔径大小可通过纳米颗粒种类和浓度调控。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a preparation method of a capillary pore high-flux cellulose composite membrane, wherein activated cellulose is added into a lithium chloride / N,N-dimethylacetamide solvent containing dispersed nanoparticles to obtain a cellulose dispersion liquid containing the nanoparticles, a matrix material is immersed in the cellulose dispersion liquid containing the nanoparticles, taken out and then immersed in a polar solvent to be gelled, and in the gelling process, the nanoparticles are self-assembled into a pore structure by gravity, and then a high-flux cellulose composite membrane based on capillary pore channels formed by surface nanoparticle stacking is obtained; the preparation method is simple, the capillary pore size is adjustable, irreversible hydrogen bond aggregation densification reducing the membrane flux in the fiber drying process is overcome, the prepared material has excellent adsorption and degradation performance on organic pollutants and high-efficiency photocatalytic self-cleaning capacity, has a significant advantage in the field of organic pollutant wastewater treatment, realizes high-value utilization of agricultural and forestry wastes, and provides a new idea and method for solving the dye wastewater pollution problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of membrane separation materials technology, specifically relating to a method for preparing a capillary high-flux cellulose composite membrane. Background Technology

[0002] Membrane separation technology has been widely used in seawater desalination, industrial wastewater treatment, food processing, and biopharmaceutical separation due to its advantages such as simple operation, low energy consumption, no phase change, and small footprint. However, traditional polymer separation membranes (such as polysulfone, polyethersulfone, and polyvinylidene fluoride) generally face a core contradiction: the incompatibility between permeate flux and selectivity. Increasing the membrane pore size to increase flux often leads to a decrease in rejection rate, while increasing the density to enhance selectivity significantly reduces water flux. In addition, the hydrophobicity of traditional polymer membranes makes them prone to organic and biological fouling during use, requiring frequent cleaning or replacement, which increases operating costs.

[0003] Cellulose is a major component of natural biomass and has excellent properties such as mechanical strength, abundant hydroxyl groups on its surface that are easy to chemically modify, natural renewability, biodegradability, and superhydrophilicity. It is an ideal green substrate for constructing high-performance separation membranes.

[0004] Currently, the main limitations of cellulose-based separation membrane preparation methods are as follows: (1) During the drying process, the membrane obtained by direct vacuum filtration is subjected to pore shrinkage and structural densification caused by strong hydrogen bonding between fibers and capillary force of water, resulting in a significant decrease in porosity and ultimately a significant limitation on water flux; (2) Chemical crosslinking methods often consume the hydrophilic hydroxyl groups on the surface of cellulose, reducing the hydrophilicity of the membrane, and the residual crosslinking agent may cause environmental and health risks; (3) Polymer blending methods face the problems of poor dispersibility of nanocellulose in organic solvents and poor compatibility with hydrophobic polymer matrices. Nanocellulose tends to be completely embedded by polymers, and cannot give full play to its surface hydrophilicity and nanochannel effect; (4) The flux of membranes prepared by interfacial polymerization is greatly limited by the dense skin layer and involves toxic organic solvents.

[0005] Therefore, there is an urgent need to develop a membrane fabrication strategy that is simple, environmentally friendly, cost-controllable, and scalable, which can effectively overcome the densification and collapse of cellulose during the drying process and precisely control the membrane's pore size, porosity, and pore connectivity, thereby significantly increasing water flux while maintaining a high rejection rate. Summary of the Invention

[0006] This invention addresses the core bottleneck of low porosity and insufficient flux in existing cellulose membranes due to hydrogen bonding densification. It provides a simple method for preparing a high-flux capillary cellulose composite membrane. Using agricultural and forestry waste biomass as raw material, high-purity cellulose is extracted through a deep eutectic solvent combined with sodium chlorite bleaching. The ordered / disordered stacking of functional nanoparticles on the surface and inside the cellulose gel, through the steric hindrance and puncture effects of the nanoparticles, prevents excessive hydrogen bonding and capillary-driven collapse between cellulose nanofibers. This allows the gaps between the nanoparticles and the cellulose fiber network to jointly construct three-dimensional interconnected capillary channels, forming a high-flux water transport pathway. Simultaneously, the construction of these channels exposes numerous active sites, significantly improving adsorption efficiency and ensuring a high retention rate of pollutants by the membrane.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a capillary high-flux cellulose composite membrane includes the following steps: (1) Activate cellulose to obtain activated cellulose; (2) Dispersion of nanoparticles: The nanoparticles were added to a mixed solvent of lithium chloride / N,N-dimethylacetamide and ultrasonically dispersed to obtain a uniform and stable dispersion. (3) Cellulose dissolution: Add activated cellulose to the dispersion in step (2) and stir vigorously until completely dissolved to obtain a cellulose dispersion containing nanoparticles. (4) Material preparation: The carrier matrix is ​​immersed in the cellulose dispersion containing nanoparticles in step (3). After the dispersion completely wets the matrix, it is taken out and then immersed in a polar solution to gel it and wash away the solvent. After freeze-drying, a high-throughput cellulose composite membrane is obtained.

[0008] Step (1) Cellulose includes defatted cotton or is extracted from biomass; the method of extraction from biomass is as follows: the crushed biomass is washed with deionized water, dried and sieved through a 60-100 mesh screen to obtain biomass powder; the washed and sieved biomass powder is added to the extraction solution and reacted at 60-100℃ for 0.5-12 hours, then washed with deionized water until neutral, treated with bleaching solution at 70-85℃ for 2-4 hours, washed with deionized water until neutral, and dried to obtain high-purity cellulose.

[0009] The biomass is one or more of the following: poplar, birch, spruce, pine, bamboo, sugarcane bagasse, rice straw, rapeseed straw, corn straw, and sunflower straw; the drying is carried out at 45-105℃ for 4-24 hours.

[0010] The extract is a mixture of a deep eutectic solvent and a co-solvent. The deep eutectic solvent is an aqueous solution containing urea or choline chloride and an acid, with a total mass concentration of 40-60% for the urea or choline chloride and the acid. The molar ratio of the acid to the urea or choline chloride is 1-3:1, and the acid is one of propionic acid, acetic acid, butyric acid, or formic acid. The co-solvent is one of p-toluenesulfonic acid, xylenesulfonic acid, sodium salicylate, or nicotinamide. The mass ratio of the deep eutectic solvent to the co-solvent is 2-3:1.

[0011] The mass of the extract is more than 10 times the mass of the biomass powder.

[0012] The bleaching solution is a sodium chlorite solution with a mass concentration of 4-8%, with acetic acid added to adjust its pH to 3.5-4.5; the mass ratio of the bleaching solution to the biomass powder is 5:1-20:1.

[0013] The method for activating cellulose in step (1) is to soak cellulose in deionized water, methanol, and dimethylacetamide sequentially for 1-2 hours, then filter and dry to obtain activated cellulose; the nanoparticles are 1% to 200% of the mass of cellulose.

[0014] The lithium chloride / N,N-dimethylacetamide solvent (LiCI / DMAc) mentioned in step (2) is prepared by mixing anhydrous lithium chloride and N,N-dimethylacetamide in a mass ratio of 8:92.

[0015] The nanoparticles in step (2) are selected from one or more of the following: metal oxide nanoparticles (titanium dioxide, zinc oxide, silicon dioxide, aluminum oxide, iron tetroxide, zirconium oxide, cerium oxide), two-dimensional layered nanomaterials (graphene oxide nanosheets, reduced graphene oxide nanosheets, MXene nanosheets, tungsten disulfide nanosheets, molybdenum disulfide nanosheets, carbon nitride nanosheets, layered bimetallic hydroxide nanosheets, montmorillonite nanosheets, mica nanosheets, vermiculite nanosheets), organic / polymer nanoparticles (chitosan nanoparticles, polyaniline nanoparticles, polypyrrole nanoparticles, covalent organic framework nanosheets / nanoparticles, metal-organic framework nanoparticles, polydopamine nanoparticles), natural mineral nanoparticles (attapulgite nanorods, halloysite nanotubes, sepiolite nanofibers, lithium diatomite nanosheets, hydroxyapatite nanoparticles), or carbon-based nanoparticles (carbon nanotubes, carbon quantum dots, nanodiamonds); the nanoparticles are 1wt% to 200wt% of the mass of nanocellulose.

[0016] In step (3), the cellulose mass fraction in the cellulose dispersion containing nanoparticles is 0.01wt%-2wt%.

[0017] The substrate material in step (4) is filter paper, cellulose acetate membrane (CA), polyethersulfone membrane (PES), mixed cellulose ester membrane (MCE), nitrocellulose membrane (NC), polyvinylidene fluoride membrane (PVDF), polytetrafluoroethylene membrane (PTFE), nylon membrane (NY), or polypropylene membrane (PP); the immersion time is more than 2 minutes to ensure that the carrier is completely wetted.

[0018] The polar solvent in step (4) is one of water, methanol, ethanol, n-alcohol, n-propanol, isopropanol, acetone, acetonitrile, or ethyl acetate; the washing liquid is one or a mixture of two polar solvents; the immersion time in the polar solvent is more than 5 minutes.

[0019] The freeze-drying in step (4) involves freezing at -20°C for 1-6 hours and then freeze-drying at -40°C for 48 hours.

[0020] The present invention has the following beneficial effects: 1. Simple method for forming capillaries: The high-flux cellulose membrane with capillaries of the present invention can be obtained through a simple impregnation and regeneration process, and its pore size can be controlled by the type and concentration of nanoparticles.

[0021] 2. High flux and high retention rate: The capillary force generated by the stacking of nanoparticles accelerates the transmembrane transport of water molecules, thereby significantly improving water flux; at the same time, the stacking channels formed by nanoparticles provide a large number of additional active sites for the cellulose gel membrane, thus ensuring the membrane's high retention rate.

[0022] 3. Renewable and biodegradable raw materials: Cellulose is derived from agricultural and forestry waste such as wood, bamboo, straw, and cotton linters, making the raw materials widely available and renewable. The entire membrane can naturally degrade at the end of its service life, without producing microplastic pollution, which aligns with the concept of a sustainable circular economy.

[0023] 4. Multifunctional integration: By selecting functional nanoparticles with catalytic activity (such as TiO2 photocatalysis, Fe3O4 Fenton catalysis, MOF catalysis), antibacterial properties (such as ZnO nanoparticles), conductivity (such as CNT, MXene, polyaniline nanoparticles), magnetic response (such as Fe3O4 nanoparticles), or adsorption properties (such as GO, LDH, COF nanoparticles), multiple functions such as catalytic degradation, antibacterial disinfection, self-cleaning, electrochemical-assisted anti-pollution, magnetic recovery, and heavy metal / organic pollutant adsorption can be integrated in addition to high-throughput separation.

[0024] 5. Excellent antifouling properties: The inherent superhydrophilicity of cellulose and the additional hydrophilic / charged surface introduced by nanoparticles form a strong hydration layer barrier on the membrane surface, which can effectively resist the non-specific adsorption of organic pollutants, oils and microorganisms. Attached Figure Description

[0025] Figure 1 The images show surface SEM images of cellulose composite films with different TiO2 nanoparticle contents in Example 1. Figure 2 SEM image of the pure cellulose membrane in Comparative Example 1; Figure 3 SEM and TEM images of a cellulose composite membrane containing 60% TiO2; Figure 4 Fourier transform infrared spectra of cellulose composite membranes with different TiO2 nanoparticle contents in Example 1 and pure cellulose membranes in Comparative Example 1. Figure 5 The N2 adsorption-desorption isotherms and pore size distribution curves are shown for cellulose composite membranes with different TiO2 nanoparticle contents in Example 1 and pure cellulose membranes in Comparative Example 1. Figure 6 The water contact angle and wetting rate of cellulose composite membranes with different TiO2 nanoparticle contents in Example 1 and pure cellulose membranes in Comparative Example 1 are compared. Figure 7 The pure water flux and RhB and CR rejection rates of the cellulose composite membrane with different TiO2 nanoparticle contents in Example 1 and the pure cellulose membrane in Comparative Example 1 are compared. Figure 8 The degradation rate of CR was measured by irradiating the membranes and filter paper substrates of cellulose composite membranes with different TiO2 nanoparticle contents in Example 1 and pure cellulose membranes in Comparative Example 1 after dark adsorption equilibrium and irradiation with ultraviolet light for 4 hours. Figure 9 The usage of a cellulose composite membrane with 60% TiO2 nanoparticle content after 5 cycles of filtration. Detailed Implementation

[0026] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0027] Example 1 A method for preparing a high-flux capillary cellulose composite membrane, the specific steps of which are as follows: (1) Material pretreatment: Weigh out 0.5 wt% of degreased cotton powder and soak it in UP water, methanol and DMAc for 2 hours in sequence (the solvent needs to completely submerge the cellulose). After each soaking, squeeze it with filter paper to obtain activated cellulose. (2) Dispersion of nanoparticles: Anhydrous LiCl was added to DMAc at a mass ratio of 8:92 to prepare LiCl / DMAc solvent; the prepared TiO2 nanoparticles were added to lithium chloride / N,N-dimethylacetamide solvent at a mass of 60wt% of the degreased cotton powder, and ultrasonically dispersed at 24KHz and 960W for 10 minutes to obtain a uniform, viscous dispersion without obvious particles. (3) Cellulose dissolution: The activated cellulose from step (1) is added to the dispersion from step (2), and stirred (for 3 days) until the cellulose is completely dissolved to obtain a cellulose dispersion containing nanoparticles; the mass fraction of defatted cotton in the dispersion is 0.5%; (4) Material preparation: Immerse the filter paper in the cellulose dispersion obtained in step (3) for 20 minutes, remove it with tweezers until the solution stops dripping, then immerse it in ethanol for 30 minutes to gel it, wash the sample multiple times with ethanol and deionized water to remove residual LiCl / DMAc, and finally freeze it in a -20℃ freezer for 3 hours and freeze-dry it in a -40℃ vacuum freeze dryer for 12 hours to obtain a capillary high-flux cellulose membrane.

[0028] In Example 1, the mass fraction of TiO2 nanoparticles relative to the defatted cotton powder was adjusted to 0%, 30%, 90%, and 120%, while other steps remained unchanged, to prepare high-flux cellulose membranes with different capillary pores.

[0029] Comparative Example 1 Preparation of pure cellulose membrane: Prepare a 0.5 wt% degreased cotton cellulose solution without adding nanoparticles. Replace the dispersion with pure cellulose solution according to step (4) of Example 1 and then proceed according to step (4) of Example 1 to obtain a pure cellulose membrane.

[0030] Pure water flux test: The fiber membrane was fixed in an area of ​​1.77 cm². 2 In a 1.5cm diameter filter, 4mL of pure water is added to the filter cup each time. The vacuum pump is turned on (maintaining a pressure of approximately -100kPa) to collect the permeate. The time taken for 4mL of pure water to permeate through the filter is recorded using a stopwatch. The pure water flux is measured in J (L·m³). -2 ·h -1 Calculate using the following formula (1): (1) J w Represents water flux, V (L), A (m³) 2 T(h) and T(h) are the filtrate volume, effective membrane area, and filtration time, respectively.

[0031] Dye Retention Rate Test: 10 mg / L Congo Red (CR) solution and Rhodamine B (RhB) solution were prepared as raw materials. The absorbance was measured at their respective maximum absorption wavelengths (498 nm for Congo Red and 554 nm for Rhodamine B) using a UV-Vis spectrophotometer. A standard working curve was plotted, and the concentration was calculated from the standard curve. The filtration performance of the membrane was tested under pure gravity filtration using the filter cup device used to test the water flux. Each 4 mL of filtrate was used as a sampling point, and the termination point was the point where the residual dye concentration remained unchanged at three consecutive adjacent sampling points. The changes in residual dye concentration and water flux were analyzed, and the corresponding breakthrough curve was plotted. The rejection rate (%) was calculated according to the following formula (2): Retention rate (%) = (C0 - C) t ) / C0×100%(2) In the formula, C0 (mg / L) is the initial concentration of the dye, C t (mg / L) represents the concentration of the dye after filtration.

[0032] Photocatalytic degradation kinetics test: Prepare a 20 mg / L Congo red solution. Weigh 10 mg of dried fiber membrane sample and place it in a 50 mL brown reagent bottle. Add 50 mL of the above dye solution and measure the initial absorbance. Place the reagent bottle in a constant temperature shaker (25℃, 160 rpm) and shake in the dark for 24 hours to reach adsorption-desorption equilibrium. Record the sample taken at this time as C0. Then turn on a 350 W mercury lamp (without a UV filter), keep stirring, and calibrate the light intensity using a photoelectric power meter. Take a 1 mL sample every half hour, filter it, and measure the absorbance. Calculate the concentration C. t The degradation rate (%) is calculated using the following formula (3): Degradation rate (%) = (1-C) t / C0)×100%(3) Where C0 is the initial equilibrium concentration, in mg / L; C t The sampling concentration is expressed in mg / L.

[0033] Cyclic performance test: A composite membrane prepared with 60% TiO2 content was subjected to five repeated adsorption-photocatalytic degradation cycles. After each cycle, the membrane was removed, its surface was gently rinsed with deionized water, and then placed in an ethanol-water solution containing 0.1 mol / L sodium hydroxide (ethanol and water were mixed at a volume ratio of 1:1 before adding sodium hydroxide) for regeneration. The regenerated membrane was then immersed in fresh Congo red solution for the next round of adsorption-degradation experiments. The degradation rate of each cycle was recorded to evaluate the membrane's reusability.

[0034] Figure 1The images show SEM images of the cellulose composite membranes with different TiO2 nanoparticle contents in Example 1: (a) 30% TiO2 content, (b) 60% TiO2 content, (c) 90% TiO2 content, and (d) 120% TiO2 content. The images show that when the TiO2 nanoparticle content is 30%, a large number of fine particles appear on the surface of the composite membrane, with a relatively uniform distribution and significantly increased surface roughness. When the TiO2 nanoparticle content reaches 60%, the particle coverage on the composite membrane surface is relatively continuous, with a small number of nanoscale gaps between the particles and slight local accumulation without forming large agglomerates. When the particle content reaches 90%, the particles on the composite membrane surface are too densely packed, and small agglomerates appear locally. When the content reaches 120%, obvious particle agglomeration occurs on the surface of the composite membrane, forming large aggregates. Therefore, it can be seen that the membrane surface structure can be controlled by changing the ratio of cellulose to nanoparticles.

[0035] Figure 2 For Comparative Example 1, SEM images of the pure cellulose membrane are shown. (a) and (b) are SEM images of the surface and cross-section of the pure cellulose membrane, respectively. The surface of the pure cellulose membrane (0%) is smooth and flat, with only some nanoscale pores formed by the drying process. The pure cellulose coating in the cross-section forms the upper and lower surfaces of the substrate material (filter paper), creating a sandwich structure. Therefore, an adhesive layer can be constructed on the substrate surface through impregnation and regeneration.

[0036] Figure 3 The images show SEM and TEM images of a cellulose membrane with 60% TiO2. (a) and (b) are SEM images of the cross-section of the cellulose composite membrane with 60% TiO2, and (c)-(f) are TEM images of the cross-section of the cellulose composite membrane with 60% TiO2. It can be seen that the upper and lower surfaces of the substrate material (filter paper) are covered with a nano-thin layer (less than 1 μm thick) formed by TiO2 nanoparticles and regenerated cellulose. The regenerated cellulose tightly locks the nanoparticles inside the thin layer, and the nanoparticles are tightly packed together to form channels. These nanoparticle-packed channels can form capillary action, changing the water mass transfer mechanism from pure gravity flow to capillary-assisted permeation, which greatly reduces the resistance to transmembrane mass transfer and is expected to accelerate water transport and thus improve membrane flux. At the same time, the photocatalytic effect of titanium dioxide nanoparticles also endows the cellulose membrane with photocatalytic function, which is expected to degrade pollutants on the membrane surface and thus achieve self-cleaning.

[0037] Figure 4 The Fourier transform infrared spectra of cellulose composite membranes with different TiO2 nanoparticle contents in Example 1 and pure cellulose membranes in Comparative Example 1 are shown. A comparison reveals that at approximately 650-700 cm⁻¹... -1Near the same location, samples containing TiO2 (30%, 60%, 90%, and 120%) all exhibited a new broad absorption band, attributed to the stretching vibration of Ti-O-Ti; in the 3400-3300 cm⁻¹ range... -1 The range belongs to the cellulose -OH absorption peak. With the increase of TiO2 nanoparticles, the hydroxyl absorption peak of the pure cellulose composite membrane sample with 0% TiO2 increases from 3404 cm⁻¹. -1 The red-shifted cellulose composite membrane sample with 120% TiO2 was at 3383.19 cm⁻¹. -1 This indicates that TiO2 nanoparticles were successfully loaded and formed hydrogen bonds with TiO2 nanoparticles, preventing the material from falling off during use and potentially enhancing its recyclability.

[0038] Figure 5 The N2 adsorption-desorption isotherms and pore size distribution curves are shown for cellulose membranes with different TiO2 nanoparticle contents in Example 1 and pure cellulose membranes in Comparative Example 1. The N2 adsorption-desorption curves of all samples follow a type IV adsorption isotherm distribution. With the increase of TiO2 nanoparticle content, the N2 adsorption capacity and BET specific surface area increase accordingly. The corresponding pore volume and pore size show a trend of first decreasing and then increasing. The above results indicate that by changing the ratio of cellulose to nanoparticles, the internal structure, pore size distribution, and capillary channel size of the composite membrane can be controlled to achieve the physical sieving effect of pore size. In addition, the addition of TiO2 nanoparticles inhibits densification during the regeneration process of pure cellulose gel membranes.

[0039] Figure 6 The water contact angle and wetting rate of the cellulose composite membrane with different TiO2 nanoparticle contents in Example 1 and the pure cellulose membrane in Comparative Example 1 were compared. With increasing TiO2 nanoparticle content, both the water contact angle and wetting rate showed a trend of first decreasing and then increasing. The initial contact angle of the pure cellulose composite membrane was 32.74°, and the wetting time was approximately 47 s. When the TiO2 nanoparticle content increased to 60%, the optimal performance was achieved with a water contact angle of 25.34° and a wetting time of only 10.13 s. When the TiO2 nanoparticle content increased to 12%, the optimal performance was achieved with a water contact angle of 25.34° and a wetting time of only 10.13 s. At 0%, the water contact angle was 33.07° and the wetting time was approximately 38.07 s. These results indicate that the capillary structure formed by nanoparticles and cellulose can regulate the wettability of the composite membrane surface, which is beneficial for the rapid penetration of water molecules and the adsorption of pollutants. Among them, the 60% TiO2 cellulose membrane has the smallest average pore size (see Table 1). According to the inverse relationship between capillary pressure and pore size, its capillary effect is the strongest, the liquid permeates faster, and thus the wetting time is the shortest. This result further confirms that the stacking of titanium dioxide forms a capillary effect, which accelerates the permeation of water.

[0040] Table 1 Pore structure parameters of the membrane

[0041] Figure 7The pure water flux and RhB (Rhodamine B) and CR (Congo Red) rejection rates of the cellulose composite membrane with different TiO2 nanoparticle contents in Example 1 and the pure cellulose membrane in Comparative Example 1 were compared. The water flux of the cellulose composite membrane first increased and then decreased with increasing TiO2 nanoparticle content, while the water flux of the pure cellulose composite membrane was 200.81 L·m. -2 ·h -1 With the TiO2 nanoparticle content increasing to 60%, the flux reached its maximum value of 479.58 L·m⁻¹. -2 ·h -1 The flux was increased by approximately 139% compared to pure cellulose membranes. Further increasing the TiO2 nanoparticle content to 90% and 120% resulted in a decrease in flux to 277.31 L·m⁻¹, respectively. -2 ·h -1 and 226.47 L·m -2 ·h -1 The pure cellulose composite membrane exhibits the highest rejection rate for both pollutants. The rejection rate remains almost unchanged with the addition of TiO2 nanoparticles, indicating that the cellulose gel membrane stacked with nanoparticles achieves a significant increase in flux while maintaining a high rejection rate, providing a solution to overcome the contradiction between high flux and high rejection rate.

[0042] Figure 8 The degradation rates of CR (carbon dioxide) were compared between Example 1 (cellulose composite membranes with different TiO2 nanoparticle contents), Comparative Example 1 (pure cellulose membrane (0% TiO2) and filter paper substrate) after 4 hours of UV irradiation following dark adsorption equilibrium. During dark adsorption, the CR removal rate of all samples was less than 20%, indicating that adsorption was not the primary pathway for pollutant treatment by the composite membranes. In the subsequent photocatalytic degradation process, the removal rates of the filter paper and pure cellulose composite membrane samples only slightly increased. The photocatalytic activity of the composite membrane significantly improved after the addition of TiO2 nanoparticles. The highest CR removal rate (83.3%) was achieved with 60% TiO2 nanoparticles, gradually decreasing thereafter. At 120% TiO2 nanoparticles, the composite membrane's removal rate was 53.4%, still significantly higher than that of the filter paper (16.2%) and pure cellulose membrane (28.8%).

[0043] Figure 9 The results of five cycles of a cellulose composite membrane with 60% TiO2 nanoparticle content showed that the membrane removal efficiency decreased slightly with increasing number of cycles, but stabilized after three cycles. This indicates that the composite membrane has a certain degree of reusability and has potential for application in actual wastewater treatment.

[0044] Example 2 A method for preparing a high-flux capillary cellulose composite membrane, the specific steps of which are as follows: (1) Material pretreatment: The bamboo powder biomass was washed 4 times with deionized water to remove the surface ash, dried at 60℃ for 12 hours, and sieved through an 80-mesh screen to obtain biomass powder. (2) Pretreatment of materials: Propionic acid and urea were mixed with water at a molar ratio of 3:1 to obtain deep eutectic solvent (DES). The total mass concentration of DES (propionic acid and urea) was 60%. DES was mixed with the cosolvent p-toluenesulfonic acid at a mass ratio of 2:1 to obtain cellulose extract. Mix 5g of bamboo powder biomass obtained in step (1) with 100g of cellulose extract and heat in an oil bath at 60°C for 12 hours. After the reaction is complete, centrifuge to separate the solid. Wash the obtained solid with deionized water until neutral. Place the obtained solid in a 6wt% sodium chlorite solution (adjust the pH to 4.5 with acetic acid). The mass ratio of 6wt% sodium chlorite solution to solid biomass powder is 10:1. Heat the mixture in an oil bath at 80°C for 3 hours. After treatment, wash the solid with deionized water until neutral and dry to obtain high-purity cellulose from bamboo powder. Weigh out 0.5 wt% of cellulose by solvent and soak it in ultrapure water, methanol, and DMAc sequentially for 2 hours (the solvent must completely submerge the cellulose). After each soaking, filter the solution to obtain activated cellulose. (3) Dispersion of nanoparticles: Anhydrous LiCl was added to DMAc at a mass ratio of 8:92 and mixed to prepare LiCl / DMAc solvent; the prepared TiO2 nanoparticles were added to lithium chloride / N,N-dimethylacetamide solvent at a mass ratio of 100wt% of cellulose and ultrasonically dispersed at 24KHz and 960W for 10 minutes to obtain a uniform, viscous dispersion without obvious particles; (4) Cellulose dissolution: The activated cellulose from step (2) is added to the dispersion prepared in step (3), and stirred (for 5 days) until the cellulose is completely dissolved to obtain a cellulose dispersion containing nanoparticles; the mass fraction of cellulose in the dispersion is 1%; (5) Material preparation: Immerse the filter paper in the cellulose dispersion obtained in step (4) for 40 minutes, remove it with tweezers until the solution stops dripping, then immerse it in ethanol for 15 minutes to gel it, wash the membrane sample multiple times with ethanol and deionized water to remove residual LiCl / DMAc, and finally freeze it in a -20℃ freezer for 6 hours and then freeze-dry it in a vacuum freeze dryer at -50℃ for 48 hours to obtain a capillary high-flux cellulose membrane.

[0045] Example 3 A method for preparing a high-flux capillary cellulose composite membrane, the specific steps of which are as follows: (1) Material pretreatment: Poplar wood powder biomass was washed three times with deionized water to remove surface ash, dried at 45℃ for 24 hours, and sieved through a 100-mesh screen to obtain biomass powder; (2) Pretreatment of materials: Propionic acid and urea were mixed with water at a molar ratio of 1:1 to obtain deep eutectic solvent (DES). The total mass concentration of DES (propionic acid and urea) was 50%. DES was mixed with the auxiliary agent p-toluenesulfonic acid at a mass ratio of 2.5:1 to obtain cellulose extract. Mix 5g of poplar wood powder biomass obtained in step (1) with 80g of cellulose extract, heat in an oil bath at 100℃ for 0.5 hours, after the reaction is completed, centrifuge to separate the solid, wash the obtained solid with deionized water until neutral, place the obtained solid in a 4wt% sodium chlorite solution (adjust the pH to 3.5 with acetic acid), the mass ratio of 4wt% sodium chlorite solution to solid biomass powder is 20:1, heat the mixture in an oil bath at 70℃ for 4 hours, wash the treated solid with deionized water until neutral, and obtain high-purity cellulose from poplar wood; Weigh out 0.5 wt% of the solvent and soak it in water, methanol, and DMAc for 1.5 hours in sequence (the solvent needs to completely submerge the cellulose). After each soaking, squeeze it with filter paper to obtain activated cellulose. (3) Dispersion of nanoparticles: Anhydrous LiCl was added to DMAc at a mass ratio of 8:92 and mixed to prepare LiCl / DMAc solvent; the prepared graphene oxide (GO) nanosheets were added to lithium chloride / N,N-dimethylacetamide solvent at a mass of 60wt% of cellulose and ultrasonically dispersed at 24KHz and 960W for 10 minutes to obtain a uniform, viscous dispersion without obvious particles; (4) Cellulose dissolution: The activated cellulose from step (2) is added to the dispersion prepared in step (3), and stirred (for 4 days) until the cellulose is completely dissolved to obtain a cellulose dispersion containing nanoparticles; the mass fraction of cellulose in the dispersion is 0.01%; (5) Material preparation: Immerse the filter paper in the dispersion obtained in step (4) for 20 minutes, remove it with tweezers until the solution stops dripping, then immerse it in ethanol for 10 minutes to gel it, wash the membrane sample multiple times with ethanol and deionized water to remove residual LiCl / DMAc, and finally freeze it in a -30℃ freeze dryer for 2 hours and freeze-dry it in a vacuum freeze dryer at -40℃ for 48 hours to obtain a capillary high-flux cellulose membrane.

[0046] Example 4 A method for preparing a high-flux capillary cellulose composite membrane, the specific steps of which are as follows: (1) Material pretreatment: The spruce wood powder biomass was washed 5 times with deionized water to remove the surface ash, dried at 105℃ for 4 hours, and then sieved through a 60-mesh screen to obtain biomass powder. (2) Pretreatment of materials: Propionic acid and choline chloride were mixed with water at a molar ratio of 2:1 to obtain deep eutectic solvent (DES). The total mass concentration of DES (propionic acid and choline chloride) was 40%. DES was mixed with the auxiliary agent toluenesulfonic acid at a mass ratio of 3:1 to obtain cellulose extract. 5g of spruce biomass obtained in step (1) was mixed with 110g of cellulose extract and heated in an oil bath at 80°C for 8 hours. After the reaction was completed, the solid was separated by centrifugation. The obtained solid was washed with deionized water until neutral and placed in an 8wt% sodium chlorite solution (pH adjusted to 4 with acetic acid). The mass ratio of 8wt% sodium chlorite solution to solid biomass powder was 5:1. The mixture was heated in an oil bath at 85°C for 2 hours. After treatment, the solid was washed with deionized water until neutral to obtain high-purity cellulose from spruce wood. Weigh out 0.5 wt% of cellulose by solvent and soak it in UP water, methanol, and DMAc for 1 hour in sequence (the solvent needs to completely submerge the cellulose). Filter after each soaking to obtain activated cellulose. (3) Dispersion of nanoparticles: Anhydrous LiCl was added to DMAc at a mass ratio of 8:92 and mixed to prepare LiCl / DMAc solvent; the prepared carbon nanotubes (CNTs) were added to lithium chloride / N,N-dimethylacetamide solvent at a mass ratio of 200wt% of cellulose and ultrasonically dispersed at 24KHz and 960W for 10 minutes to obtain a uniform, viscous dispersion without obvious particles; (4) Cellulose dissolution: The activated fiber from step (2) is added to the particle dispersion prepared in step (3), and stirred (for 6 days) until the cellulose is completely dissolved to obtain a cellulose dispersion containing nanoparticles; the mass fraction of cellulose in the dispersion is 2%; (5) Preparation of materials: Immerse the cellulose acetate membrane in the cellulose dispersion obtained in step (4) for 30 minutes, remove it with tweezers until the solution stops dripping, then immerse it in ethanol for 5 minutes to gel it, wash the membrane sample multiple times with ethanol and deionized water to remove residual LiCl / DMAc, and finally freeze it in a -25℃ freeze dryer for 1 hour and freeze-dry it in a vacuum freeze dryer at -40℃ for 48 hours to obtain a capillary high-flux cellulose membrane.

[0047] The specific embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A method for preparing a high-flux capillary cellulose composite membrane, characterized in that, Includes the following steps: (1) Activate cellulose to obtain activated cellulose; (2) The nanoparticles were added to a mixed solvent of lithium chloride / N,N-dimethylacetamide and ultrasonically dispersed to obtain a dispersion. (3) Add activated cellulose to the dispersion and stir until completely dissolved to obtain a cellulose dispersion containing nanoparticles; (4) The matrix material is immersed in a cellulose dispersion containing nanoparticles, then immersed in a polar solution to gel it and wash away the solvent. After freeze-drying, a high-throughput cellulose composite membrane is obtained.

2. The method for preparing the capillary high-flux cellulose composite membrane according to claim 1, characterized in that, Step (1) Cellulose is degreased cotton or extracted from biomass; the method of extraction from biomass is as follows: wash the crushed biomass with deionized water, dry it and sieve it through a 60-100 mesh screen to obtain biomass powder; add the washed and sieved biomass powder to the extraction solution, react at 60-100℃ for 0.5-12 hours, then wash it with deionized water until neutral, treat it with bleaching solution at 70-85℃ for 2-4 hours, wash it with deionized water until neutral, and dry it to obtain high-purity cellulose.

3. The method for preparing the capillary high-flux cellulose composite membrane according to claim 2, characterized in that, The biomass is one or more of the following: poplar, birch, spruce, pine, bamboo, sugarcane bagasse, rice straw, rapeseed straw, corn straw, or sunflower straw; the drying is carried out at 45-105℃ for 4-24 hours.

4. The method for preparing the capillary high-flux cellulose composite membrane according to claim 2, characterized in that, The extract is a mixture of a deep eutectic solvent and a co-solvent. The deep eutectic solvent is an aqueous solution containing urea or choline chloride and an acid, with a total mass concentration of 40-60% and a molar ratio of acid to urea or choline chloride of 1-3:

1. The acid is one of propionic acid, acetic acid, butyric acid, or formic acid. The co-solvent is one of p-toluenesulfonic acid, xylenesulfonic acid, sodium salicylate, or nicotinamide. The mass ratio of the deep eutectic solvent to the co-solvent is 2-3:

1. The mass of the extract is more than 10 times the mass of the biomass powder.

5. The method for preparing the capillary high-flux cellulose composite membrane according to claim 2, characterized in that, The bleaching solution is a sodium chlorite solution with a mass concentration of 4-8%, with acetic acid added to adjust its pH to 3.5-4.5; the mass ratio of the bleaching solution to the biomass powder is 5:1-20:

1.

6. The method for preparing the capillary high-flux cellulose composite membrane according to claim 1, characterized in that, The method for activating cellulose in step (1) is to soak cellulose in deionized water, methanol, and dimethylacetamide sequentially for 1-2 hours and then filter it to obtain activated cellulose.

7. The method for preparing the capillary high-flux cellulose composite membrane according to claim 1, characterized in that, The nanoparticles in step (2) are selected from one or more of metal oxide nanoparticles, two-dimensional layered nanomaterials, organic / polymer nanoparticles, natural mineral nanoparticles or carbon-based nanoparticles; the nanoparticles are 1% to 200% of the mass of cellulose; the lithium chloride / N,N-dimethylacetamide solvent is prepared by mixing anhydrous lithium chloride and N,N-dimethylacetamide in a mass ratio of 8:

92.

8. The method for preparing the capillary high-flux cellulose composite membrane according to claim 1, characterized in that, In step (3), the cellulose mass fraction in the cellulose dispersion containing nanoparticles is 0.01%-2%.

9. The method for preparing the capillary high-flux cellulose composite membrane according to claim 1, characterized in that, The matrix material in step (4) is filter paper, cellulose acetate membrane, polyethersulfone membrane, mixed cellulose ester membrane, nitrocellulose membrane, polyvinylidene fluoride membrane, polytetrafluoroethylene membrane, nylon membrane or polypropylene membrane; the immersion time is more than 2 minutes.

10. The method for preparing the capillary high-flux cellulose composite membrane according to claim 1, characterized in that, The polar solvent in step (4) is one of water, methanol, ethanol, n-alcohol, n-propanol, isopropanol, acetone, acetonitrile, and ethyl acetate; the washing liquid is one or two polar solvents mixed together; the immersion time in the polar solvent is more than 5 minutes; the freeze drying is performed by freezing at -20°C for 1-6 hours and then freeze-drying at -40°C for 48 hours.